Effectiveness of Clinical Learning Methods in Improving Clinical Skills of Nursing Students: Systematic Review - Muhammad Al-amin R. Sapeni; Kadek Ayu Erika; Ariyanti Saleh (Indonesian Contemporary Nursing Journal, 2020)
Introduction: Clinical skills are an important indicator that must be achieved in the application of clinical learning to nursing students. Method: The design of this study is a systematic review. This article was prepared in accordance with the PRISMA method. Search for articles using the Pubmed, Proquest, ScienceDirect, and Ebsco databases. Research questions were prepared using the PICO method, and search keywords were based on a database in MeSH Term. The inclusion criteria in this review article are the focus on the application of clinical learning methods, applied to nursing students, the type of Randomized Controlled Trial research, influencing clinical skills, and published since 2011-2020.  There were 2,078 articles found. The included articles were analyzed using the Critical Appraisal Skills Program. To assess the quality of articles used the Effective Public Health Practice Project. Result: There are six articles included in this study. From the results of the critical assessment in the included article, the application of Flipped Learning, Video Skills, Interactive Clinical Nursing Skills Mobile Applications, High-Fidelity, Clinical Teaching Associates, End-of-Life Care can significantly improve the clinical skills of nursing students. Conclusion: The clinical learning methods applied can improve the clinical skills of nursing students. Therefore, these clinical learning models can be recommended in nursing education.